2020
DOI: 10.1101/2020.04.01.019539
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-183/96/182 cluster is an important morphogenetic factor targetingPAX6expression in differentiating human retinal organoids

Abstract: MicroRNAs (miRNAs), a class of small, non-coding RNA molecules represent important regulators of gene expression. Recent reports have implicated their role in the cell specification process acting as "fine-tuners" to ensure the precise gene expression at the specific stage of cell differentiation. Here we used retinal organoids differentiated from human pluripotent stem cells (hPSCs) as a model to closely investigate the role of a sensory organ-specific and evolutionary conserved miR-183/96/182 cluster. Using … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…The detection and expression patterns of these markers highlight extensive laminar formation by day 35, as described in previous studies, suggesting high replicability of this protocol to generate hiPSC-derived ocular vesicles faithful to human eye development. 22,32,[38][39][40] Importantly, we detect the expression of more mature photoreceptor and retinal ganglion cell progenitor markers such as CRX, OTX2 and BRN3b by day 50, suggesting this protocol can generate retinal lineage-specific organoids. Similar expression patterns have been detected in human foetal tissue (HFT), suggesting a high fidelity between in vitro optic vesicles and HFT.…”
Section: Discussionmentioning
confidence: 75%
“…The detection and expression patterns of these markers highlight extensive laminar formation by day 35, as described in previous studies, suggesting high replicability of this protocol to generate hiPSC-derived ocular vesicles faithful to human eye development. 22,32,[38][39][40] Importantly, we detect the expression of more mature photoreceptor and retinal ganglion cell progenitor markers such as CRX, OTX2 and BRN3b by day 50, suggesting this protocol can generate retinal lineage-specific organoids. Similar expression patterns have been detected in human foetal tissue (HFT), suggesting a high fidelity between in vitro optic vesicles and HFT.…”
Section: Discussionmentioning
confidence: 75%
“…The miR-183-96-182 cluster is well known to be a typical miRNA cluster because its three components have similar seed sequences and common target genes, and even play similar biological functions [10,14]. In the present study, we demonstrated that the miR-183-96-182 cluster members may share a common promoter, which is activated by the same Increasing evidence suggests that the miR-183-96-182 cluster has a common putative promoter in humans [4,30,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that miRNA clusters are prevalent in various organisms (Drosophila melanogaster, 50%; humans, 25%) and are highly conserved among different species [6]. Owing to the sharing of common promoters, members of a cluster are usually regulated by the same factors and show similar expression profiles [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cluster is expressed in embryonic stem cells, and in the inner ear[11] and retina[12]. It was also observed that a temporal reduction in the expression of miR183 cluster is necessary for epidermal differentiation to neuroectodermal lineage[13].…”
Section: Introductionmentioning
confidence: 99%